The Effect of the Think-Pair-Share (TPS) Learning Model Assisted by PhET Simulation on Fifth-Grade Students' Learning Outcomes in Simple Machines - Ananda Dwi Putri; Zulherman Zulherman (Journal of Educational Sciences, 2026)
Learning outcomes in elementary science, particularly on simple machines, remain unsatisfactory because students often experience difficulties in understanding abstract concepts through conventional instruction. This study aimed to determine the effect of the Think-Pair-Share (TPS) learning model assisted by PhET Simulation on fifth-grade students’ learning outcomes in simple machines. This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. A total of 104 fifth-grade students from four intact classes in two elementary schools were selected through purposive sampling, comprising two experimental classes and two control classes. Data were collected using a 38-item multiple-choice achievement test administered as pretests and posttests. The data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, Levene’s homogeneity test, the Mann–Whitney U test, and Cohen’s d effect size analysis. The experimental group achieved a higher mean posttest score of 28.08 out of 38 than the control group, which achieved 17.69 out of 38. The Mann–Whitney U test indicated a significant difference between the groups (p < 0.001), while Cohen’s d of 1.413 indicated a large effect. These findings indicate that TPS assisted by PhET Simulation is effective for improving students’ learning outcomes in simple machines.